2017
DOI: 10.1016/j.engstruct.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage modelling approach for the analysis of the stress distribution in anchorage zones of pre-tensioned, concrete elements

Abstract: An innovative strategy for the analysis and design of the anchorage zones of pre-tensioned, concrete girders is presented. In this approach, the bond behaviour of the prestress strands is first characterised in a small-sized beam model. A new relation between the slip and radial strain of the prestress strand is introduced and used together with the radial stress-strain relation resulting from a thick-walled cylinder model to establish the bond-slip behaviour at the steel-concrete interface. This bond behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several earlier studies [3] showed that the main cause of horizontal end cracking is the transferring of prestressing forces from tendons to the surrounding concrete that results in stress concentration at the end-zone of the element and the control of these stresses is quite a challengeable task [3,5]. The transfer of prestressing forces from strands to concrete at the end-zone of PC-girders result in a complex stress state that can lead to concrete cracking [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies [3] showed that the main cause of horizontal end cracking is the transferring of prestressing forces from tendons to the surrounding concrete that results in stress concentration at the end-zone of the element and the control of these stresses is quite a challengeable task [3,5]. The transfer of prestressing forces from strands to concrete at the end-zone of PC-girders result in a complex stress state that can lead to concrete cracking [14].…”
Section: Introductionmentioning
confidence: 99%
“…Prestressed members are highly recommended in view of cost-effective casting in plants under higher quality control, and their durability as low maintenance structures [1]. Although, it is well-known that prestressed concrete functions well for large spans, field observations and experimental studies showed that, some types of these prestress elements exhibit horizontal end cracking due to large prestressing forces [3]. The cracks develop during the girder fabrication [4] and appear right after the prestress release process and they become noticeable at the time of lifting the girders from the prestressing bed [5].…”
Section: Introductionmentioning
confidence: 99%
“…, 1983). In fact, local compression problems of concrete sometimes directly determine the structural safety and overall reliability, affecting the normal use and service life of buildings (Li and Yu, 2015; Steensels et al. , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Local concentrated pressure will form vertical compression and lateral expansion in concrete, resulting in extremely complex local stress and deformation (Hawkins, 1970;Wang et al, 2022;Liu et al, 1983). In fact, local compression problems of concrete sometimes directly determine the structural safety and overall reliability, affecting the normal use and service life of buildings (Li and Yu, 2015;Steensels et al, 2017). Therefore, strengthening local compression zone has become an important research direction and attracted a considerable number of academics to study.…”
Section: Introductionmentioning
confidence: 99%
“…This method of modelling affects the stresses and the transmission lengths such that the model becomes irrelevant. Steensels et al [20] propose a new method of designing anchorage zones. Essentially, the strands are modelled in greater detail in terms of interaction between these elements and the concrete, with a focus on the pitch and lack-of-fit effects of the strands.…”
Section: Introductionmentioning
confidence: 99%